Hiking Gears Comparing System (HGCS) using web scraping technique / Azrul Nazrin Hamdan - Azrul Nazrin Hamdan (2017)
This project is about the development of Hiking Gears Comparing System (HGCS) for people who love to do hiking activity around Malaysia. Hiking is one of the favorite outdoor activities in Malaysia. One of the factors of people tend to carry out hiking activity is because the Malaysia landform that has many hills and mountain. So, people in Malaysia like this challenging activity to fulfill their interest and care about their healthiness. In order to carry out this activity, hikers need to use the suitable equipment or gears. Hiking gears consist of hiking backpacks, hiking footwear, hiking clothing, tents and survival kit. Hikers normally buys the hiking gears either walk in at the shop or buy through online. The problems that have been identified when the hikers want to buy the hiking gears, most of them do not know the best websites that promote the best products based on the price and the functionality. They need to open many websites to make a survey for the products that they want to buy. HGCS used the web scraping technique to extract the data from the websites that provide hiking gears. This technique has been identified in the knowledge acquisition phase. From the extracted data, HGCS will compare the products based on price, product category and functionality. This project applied the waterfall model methodology. The phases included in this project is knowledge acquisition, requirement gathering and analysis, design and implementation. Findings and analysis was done to ensure that the objectives of this project are tally with the phases in methodology. For the future work, this system may include some others outdoor activities gears, for example, rock climbing gears, cycling gears or kayaking gears. In addition, extract data from more websites that sell the hiking gears by using the web scraping technique.